Switched Semilogarithmic Quantization of Gaussian Source with Low Delay - Mosic, A.; Peric, Z.; Savic, M.; Panic, S. (Elektronika ir Elektrotechnika, 2011)
In this paper, a novel companding model based on nonuniform scalar quantization switching technique of Gaussian source is presented. A - law compandor implementation is observed. This scalar quantization model, with quantizers adapted to the maximal amplitudes of input signals, provides higher quality of signal-to-quantization noise ratio in a wide range of signal volumes, with respect to it’s necessary robustness over a broad range of input variances. The main contribution of this model is achieving higher quality of transmission and possibility of its applying for digitalization of continuous signals in wide range. Ill. 5, bibl. 8, tabl. 1 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.108.2.148